if p(x) = x + 3then p(x) + p(-x) is equal to
Asked by akshatkumar1506 | 27th May, 2019, 09:33: AM
Given : p(x) = x + 3
Put x = -x
→ p(-x) = -x + 3
p(x) + p(-x) = x + 3 - x + 3 = 6
6 is the correct answer.
Please check your options.
Answered by Yasmeen Khan | 27th May, 2019, 09:41: AM
- Factorise 2y3+y2-2y-1
- What is variable and content?
- what is standard form?
- how will I write z^3+z^4+z^5-6 in standard form ? can you help me
- what is constant polynomial
- In the following expression which expression are ponal polynomial and which are not justify your statement with answer 1. x5-3x2-5x
- Is 3/4 a polynomial?
- X=c√b+4find x+1/x
- What is the zero of the zero polynomial?
Kindly Sign up for a personalised experience
- Ask Study Doubts
- Sample Papers
- Past Year Papers
- Textbook Solutions
Verify mobile number
Enter the OTP sent to your number